Multiple-goal management: An examination of simultaneous pursuit of a weight-loss goal with another goal - McKee, H.; Ntoumanis, Nikos (Sage Publications Ltd, 2014)
This study investigated the characteristics contributing to successful goal attainment of a weight-loss and a non-weight-loss goal simultaneously. Weight-loss and non-weight-loss goals, self-efficacy, persistence, temptations, intergoal interference and facilitation were measured via an online questionnaire (N = 103, Mage = 25.36 ± 6.9, 80% women). Weight-loss self-efficacy, persistence, temptations and intergoal facilitation significantly predicted weight-loss goal attainment. Those who were more successful in attaining both their goals simultaneously had higher self-efficacy and persistence and experienced less temptation towards both goals. This study provides an insight into the characteristics necessary for successful simultaneous management of a weight-loss goal with another goal.